1959
DOI: 10.1161/01.res.7.2.238
|View full text |Cite
|
Sign up to set email alerts
|

Response of Subcutaneous Vessels to Venous Distention

Abstract: Direct observations of circulation in small vessels of the bat wing indicated that increased resistance to arterial flow could be produced by venous distention without active vasoconstriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1964
1964
1990
1990

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In earlier experiments, intravenous injections of buffered saline in much larger amounts (0.2 ml) did not affect contractile activity in arteriolar vessels, so presumably the injected saline was not responsible for the enhanced activity. 5 Microscopic observation of the cannulated artery from the cannula tip to the area selected for recording activity in a terminal arteriole showed that the infusion of buffered saline caused the oncoming blood to be forced away from the cannula tip, and as pressure continued to rise in the perfusion system, the column of blood was pushed back upstream by the column of saline. The forward flow of arterial blood was diverted into arterial branches proximal to the cannula.…”
Section: Contractile Activity In Terminal Arterioles During Continuoumentioning
confidence: 99%
“…In earlier experiments, intravenous injections of buffered saline in much larger amounts (0.2 ml) did not affect contractile activity in arteriolar vessels, so presumably the injected saline was not responsible for the enhanced activity. 5 Microscopic observation of the cannulated artery from the cannula tip to the area selected for recording activity in a terminal arteriole showed that the infusion of buffered saline caused the oncoming blood to be forced away from the cannula tip, and as pressure continued to rise in the perfusion system, the column of blood was pushed back upstream by the column of saline. The forward flow of arterial blood was diverted into arterial branches proximal to the cannula.…”
Section: Contractile Activity In Terminal Arterioles During Continuoumentioning
confidence: 99%
“…In translucent tissue it is possible to visualize a vein and to estimate its diameter by use of a microscope. This technique has been used to study venous responses in a bat's wing (Wiedeman 1959). An alternative approach which can be applied to non-translucent tissue and to deeper vessels is to inject a radio-opaque dye into a vessel and to estimate its diameter radiographically (Morris et al 1974).…”
Section: Direct Observation Of Cutaneous Veinsmentioning
confidence: 99%
“…In studies of microcirculation involving surgical denervation of blood vessels in bat wings (8)(9)(10), microscopic observation of the vessels following denervation revealed that (1) major arterial vessels increased markedly in diameter following denervation; (2) small arterial vessels such as arterioles and terminal arterioles did not show such an increase; 84 WIEDEMAN (3) major arterial vessels lost their ability to contract in circumstances which had previously provoked active contraction; and (4) small arterial vessels continued to contract spontaneously after denervation. It appeared that only the large arterial vessels were rendered inactive by denervation, and it was assumed that only they were predominantly under nervous control.…”
mentioning
confidence: 99%